STUDENTS’ PERCEPTION IN A BLENDED LEARNING SPEAKING CLASS - Desi Ike Sari (Bandar Lampung University (UBL), 2016)
Technology is one of the ways to improve education and now it is not something strange in the world.This research aimed in describing students’ perception in a blended learning, the combination of face to face classroom and online class by using Schoology for speaking skill. The study was conducted with twenty-six students of second semester in Bandar Lampung University. The data colleted by using questionnaire,the questionnaire was posted after the materials have been done by students. The questionnaire was posted in Schoology through Google forms website. The finding of the research revealed that blended learning is categorized as a something new for the students but this environment makes easier in students understanding.